Prediction Of Infant Mortality Using The Decission Tree And Genetic Algorithm Methods - Suhardjono Suhardjono; Adjat Sudradjat; Bilal Abdul Wahid; Hari Sugiarto; Hafis Nurdin (Paradigma, 2023)
One of the things that plays a role in reducing infant mortality is the government. Based on infant mortality data in Jakarta in 2018 that has been previously tested with the decision tree algorithm, the update in this study is to use the genetic algorithm. The purpose of the update is to increase the accuracy of the results to be maximized. From the test results with the DT algorithm optimized by GA, the maximum accuracy value is 100%, and each attribute has a weight value of 1 where the value is the maximum value. After obtaining maximum results, the data will be used to reduce infant mortality, especially in Jakarta